Pleural Fluid GSDMD Is a Novel Biomarker for the Early Differential Diagnosis of Pleural Effusion - Li, Pu; Shi, Jing; Zhou, Lijing; Wang, Bo; Zhang, Li Jun; Duan, Liang; Hu, Qin; Zhou, Xiaolan; Yuan, Yuan; Li, Dandan; Chen, Hong; Zhao, Qing; et al. (Frontiers in Microbiology, 2021)
Objective Gasdermin D (GSDMD), controlling pyroptosis in cells, has multiple physiological functions. The diagnostic role of GSDMD in pleural effusion (PE) remains unknown. Methods Sandwich ELISA kits that we developed were applied to measure the level of GSDMD for 335 patients with a definite cause of PE, including transudative PE, tuberculous pleural effusion (TPE), parapneumonic pleural effusion (PPE), and malignant pleural effusion (MPE). The diagnostic accuracy of Light’s criteria vs. the new marker GSDMD was performed. Clinical follow-up of 40 cases of PPE was conducted and divided into efficacy and non-efficacy groups according to the therapeutic outcome. Nucleated cells (NCs) in PE were isolated and further infected with bacteria to verify the cell source of GSDMD. Results The diagnostic accuracy of GSDMD for the diagnosis of PE were 96% (sensitivity) and 94% (specificity). The receiver operating characteristic (ROC) curve indicated that GSDMD can be an efficient biomarker for the differential diagnosis of transudative PE and other groups (all AUC > 0.973). Noteworthily, the highest AUC belonged to tuberculosis diagnosis of 0.990, and the cut-off value was 18.40 ng/mL. Moreover, the same cut-off value of PPE and MPE was 9.35 ng/mL. The combination of GSDMD, adenosine deaminase (ADA), and lactate dehydrogenase (LDH) will further improve the diagnostic efficiency especially between TPE and PPE (AUC = 0.968). The AUC of GSDMD change at day 4, which could predict the therapeutic effect at an early stage, was 0.945 (P < 0.0001). Interestingly, bacterial infection experiments further confirm that the pleural fluid GSDMD was expressed and secreted mainly by the NCs. Conclusion GSDMD and its combination are candidates as a potentially novel biomarker not only to separate PEs early and effectively, but also monitor disease progression.